COMPARING SARTORIAL INDICES: COSTUME AND COURTLY CULTURE IN MING CHINA AND MUGHAL INDIA - Murali, Anu Shree; Gupta, Vidita (PEOPLE: International Journal of Social Sciences, 2019)
Mughal India and Ming China, two of the greatest empires in medieval Asia, were successful in influencing the cultures of their respective territories and beyond. Although the two empires differed on many grounds like art, society, environment etc., there are nonetheless striking similarities between the two. These similarities are often overshadowed and neglected because of the differences. One such similarity is the clearly defined social hierarchy in the society, articulated explicitly in the functioning of the court, of both these empires. An individual’s attire in Ming China clearly reflected his/her position in the courtly hierarchy. Building on this, we tried to look at the role played by attire in establishing social rank in an equally powerful and hierarchical empire of the Mughals in India. Utilizing both primary as well as secondary sources for the purpose of this study, we have tried to bring out parallels in both the empires on practices related to attire or material possessions that led to the nurturing or establishment of social hierarchy. We could observe that, although attire facilitated the establishment of hierarchy in both the empires, the degree to which it affected the court varied. Our primary sources include contemporary political texts of the period such as “Ain-i-Akbari” and “Da Ming Hui Dian” along with the study of Mughal miniature paintings and classical portraits belonging to the Ming era. During the course of research, we also realized, little work has been done on the relation between attire and social hierarchy, especially in the context of these two empires. Existing scholarship on the subject is mostly by historians of art or fashion specifically. Thus, we believe our work will add to the emerging research on the topic, and takes into view a new perspective to clothing, which is not limited to certain streams of history.